Biomarkers and genetic polymorphisms associated with maximal fat oxidation during physical exercise: implications for metabolic health and sports performance - Chávez-Guevara, I. A.; Hernández-Torres, R. P.; González-Rodríguez, E.; Ramos-Jiménez, A.; Amaro-Gahete, F. J. (European Journal of Applied Physiology, 2022)
The maximal fat oxidation rate (MFO) assessed during a graded exercise test is a remarkable physiological indicator associated with metabolic flexibility, body weight loss and endurance performance. The present review considers existing biomarkers related to MFO, highlighting the validity of maximal oxygen uptake and free fatty acid availability for predicting MFO in athletes and healthy individuals. Moreover, we emphasize the role of different key enzymes and structural proteins that regulate adipose tissue lipolysis (i.e., triacylglycerol lipase, hormone sensitive lipase, perilipin 1), fatty acid trafficking (i.e., fatty acid translocase cluster of differentiation 36) and skeletal muscle oxidative capacity (i.e., citrate synthase and mitochondrial respiratory chain complexes II-V) on MFO variation. Likewise, we discuss the association of MFO with different polymorphism on the ACE, ADRB3, AR and CD36 genes, identifying prospective studies that will help to elucidate the mechanisms behind such associations. In addition, we highlight existing evidence that contradict the paradigm of a higher MFO in women due to ovarian hormones activity and highlight current gaps regarding endocrine function and MFO relationship.